2014
DOI: 10.1038/aps.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SKF83959 on the excitability of hippocampal CA1 pyramidal neurons: a modeling study

Abstract: Aim: 3-Methyl-6-chloro-7,8-hydroxy-1-(3-methylphenyl)-2,3,4,5-tetrahydro-1H-3-benzazepine (SKF83959) have been shown to affect several types of voltage-dependent channels in hippocampal pyramidal neurons. The aim of this study was to determine how modulation of a individual type of the channels by SKF83959 contributes to the overall excitability of CA1 pyramidal neurons during either direct current injections or synaptic activation. Methods: Rat hippocampal slices were prepared. The kinetics of voltage-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…75 Unlike E1R, which is selective for the sigma-1 receptor, SKF83959 has inherent D 1 dopamine receptor affinity among other activities. 7680 In an effort to ablate these off-target interactions, a series of modifications were performed, bringing to fruition SOMCL668, which exhibited no appreciable activity at the dopamine 1(D 1 ), D 2 , D 3 , 5-hydroxytryptamine 1A (HT), or 5-HT 2A receptors. 81,82 …”
Section: Sigma-1 Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…75 Unlike E1R, which is selective for the sigma-1 receptor, SKF83959 has inherent D 1 dopamine receptor affinity among other activities. 7680 In an effort to ablate these off-target interactions, a series of modifications were performed, bringing to fruition SOMCL668, which exhibited no appreciable activity at the dopamine 1(D 1 ), D 2 , D 3 , 5-hydroxytryptamine 1A (HT), or 5-HT 2A receptors. 81,82 …”
Section: Sigma-1 Receptormentioning
confidence: 99%
“…SKF83959 afforded improved binding and an increased PAM effect relative to that of phenytoin, a classic sigma-1 receptor PAM. , In an additional study, it was demonstrated that SFK83959 enhanced the binding activity of dehydroepiandrosterone, an endogenous agonist for the sigma-1 receptor . Unlike E1R, which is selective for the sigma-1 receptor, SKF83959 has inherent D 1 dopamine receptor affinity among other activities. In an effort to ablate these off-target interactions, a series of modifications were performed, bringing to fruition SOMCL668, which exhibited no appreciable activity at the dopamine 1­(D 1 ), D 2 , D 3 , 5-hydroxytryptamine 1A (HT), or 5-HT 2A receptors. , …”
Section: Sigma-1 Receptormentioning
confidence: 99%
“…Recently, two novel sigma-1 receptor allosteric modulators, SKF83959 and ER1, have been identified in our laboratory [14] and by another group [15]. Although SKF83959 is a very potent sigma-1 receptor allosteric modulator, the selectivity is relatively weak because SKF83959 has D 1 dopamine receptor affinity and other activities [16][17][18][19][20]. To eliminate the potential effects of SKF83959 on the D 1 and serotonin receptors, we conducted a series of structural modifications and developed the new compound 3-methyl-phenyl-2, 3, 4, 5-tetrahydro-1H-benzo[d]azepin-7-ol (SOMCL-668), referred to as SOMCL-668 (Figure S1).…”
Section: Introductionmentioning
confidence: 99%